Glass article

By placing a coating film and a shielding layer on the glass substrate, and controlling the interface porosity and Bi/Si ratio, the problem of peeling and whitening of glass articles at high temperatures is solved, and excellent adhesion and appearance performance are achieved.

CN119654298APending Publication Date: 2025-03-18AGC INC
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202380054307.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-02
Filing Date
2023-07-28
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

After existing glass items are heated and formed at high temperatures, they are prone to peeling or whitening, affecting their adhesion and appearance.

Method used

By sequentially placing the coating film and the shielding layer on the glass substrate, and controlling the void ratio at the interface portion between the coating film and the shielding layer to be less than 24%, ensuring that the maximum length of the void is less than 2.5 μm, and adjusting the Bi/Si ratio in the shielding layer to be more than 3.9 to increase the melting start temperature.

Benefits of technology

It effectively suppresses the peeling and whitening of the layer after heating and forming at high temperatures, improves the adhesion and appearance of glass items, and can maintain performance during long-term use.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119654298A_ABST
    Figure CN119654298A_ABST
Patent Text Reader

Abstract

Provided is a glass article which is capable of suppressing the occurrence of peeling or whitening of each layer disposed on a glass substrate even after long-term use after thermoforming at a high temperature, and which has excellent adhesion and appearance of each layer. A glass substrate (1) is provided with a coating film (2) and a shielding layer (3) in this order, and the porosity at an interface portion (5) between the coating film (2) and the shielding layer (3) is 24% or less. The Bi / Si ratio in the shielding layer (3) is preferably 3.9 or more. The coating film (2) is preferably a dry coating film. This glass article can be used as a window glass for an automobile.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to glass articles, in particular glass articles for vehicles. Background Art

[0002] Glass articles including window glass for vehicles or buildings are provided with desired properties by coating the surface of a glass substrate with various materials depending on the application.

[0003] Patent Document 1 discloses a glass article having a low-emissivity coating film and a shielding layer coated with black pigment, glass frit, etc. on a substrate. The shielding layer is usually provided at the peripheral portion of a glass article for a vehicle (e.g., a window glass for a car) for the purpose of preventing adhesive degradation caused by sunlight and improving appearance. Prior art literature Patent Literature

[0004] Patent Document 1: International Publication No. 2021 / 107707 Summary of the invention Technical problem solved by the invention

[0005] When the glass article of the structure described in Patent Document 1 is formed at a high temperature (e.g., 600° C. or higher) according to the intended use, the following phenomenon may occur. That is, the layers (e.g., shielding layer) disposed on the glass substrate may peel off, or the surface of the glass article may appear white (bleached) and the appearance may be impaired due to the influence of the voids formed during the heat forming process. In addition, even if the glass article is not observed to peel off the layers immediately after being heat formed at a high temperature, the layers may peel off during repeated use for a long time.

[0006] The present invention has been made in view of the above problems, and an object of the present invention is to provide a glass article in which the layers disposed on a glass substrate are prevented from peeling or whitening even after long-term use after being heat-formed at high temperature, and the layers have excellent adhesion and appearance. Solutions to technical problems

[0007] The glass article disclosed in the present invention has a coating film and a shielding layer in this order on a glass substrate, and the porosity at the interface between the coating film and the shielding layer is 24% or less. In the above glass article, the longest length of pores at the interface between the coating film and the shielding layer may be 2.5 μm or less. In any of the above-mentioned glass articles, the Bi / Si ratio in the shielding layer may be greater than 3.9. In any of the above glass articles, the Bi / Si ratio in the shielding layer may be greater than 4.7. In any of the above-mentioned glass articles, the melting start temperature of the crystalline component constituting the shielding layer may be 600° C. or higher. In any of the above glass articles, the coating film may be a dry coating film. In any of the above-mentioned glass articles, the dry coating film may be a film selected from a heat ray reflecting coating film, a low-emissivity coating film, a low-reflection coating film, and a p-polarized light reflecting coating film. In any of the above-mentioned glass articles, the pores disposed on the glass substrate may be concentrated in the interface portion between the coating film and the shielding layer compared to other portions. In any of the above-mentioned glass articles, the pores arranged on the glass substrate may have a non-uniform shape. In any of the above-mentioned glass articles, the cross-sectional shape of the holes when cut perpendicularly to the glass substrate may be a flat shape, a polygonal shape, or an irregular shape. Any of the above-mentioned glass articles can be used as window glass for automobiles. Effects of the Invention

[0008] According to the present invention, there is provided a glass article in which the layers disposed on a glass substrate are prevented from peeling off or whitening even after long-term use after being heat-formed at a high temperature, and the layers have excellent adhesion and appearance. BRIEF DESCRIPTION OF THE DRAWINGS

[0009] Figure 1A is a schematic cross-sectional view of one embodiment of a glass article of the present disclosure. Figure 1B is a schematic front view of one embodiment of a glass article of the present disclosure. Figure 2 This is an example of a cross-sectional SEM image of the glass article of the present disclosure produced in Example 3. Figure 3 This is an example of a cross-sectional SEM image of the glass article produced in Example 8. DETAILED DESCRIPTION

[0010] In the present specification, "to" indicating a numerical range means that the numerical values ​​described before and after it are included as the lower limit and the upper limit. In the numerical range recorded in the classification in this specification, the upper limit or lower limit recorded in one numerical range can also be replaced by the upper limit or lower limit of the numerical range recorded in other classifications. In addition, in the numerical range recorded in this specification, the upper limit or lower limit of the numerical range can also be replaced by the value shown in the embodiment.

[0011] As described above, when the glass article of the structure described in Patent Document 1 is heat-formed at a high temperature, the interfaces of the layers disposed on the glass substrate, such as the coating film and the shielding layer, may be delaminated, or the surface of the glass article may be whitened due to voids generated during the forming process. In addition, even if the layer delamination is not observed immediately after the heat forming, the layer delamination may occur after a certain period of time.

[0012] The present inventors speculate that the peeling and whitening caused by the heat forming operation (and cooling as needed) or during use are caused by the following reasons. That is, during the formation of the coating film, the gas contained in the coating film is degassed during heating and is retained at the interface between the coating film and the shielding layer, thereby eventually forming pores (voids). Then, the generated pores cause a decrease in interfacial adhesion, resulting in layer peeling, and further, light scattering due to the generated pores, so that when the glass article is observed from the side where the shielding layer is not arranged, a phenomenon (whitening) occurs in which it looks white.

[0013] The present inventors have conducted intensive studies and found that by setting the porosity at the interface between the coating film and the shielding layer within a specific range, it is possible to suppress the occurrence of layer separation and whitening during heat forming or after a certain period of time.

[0014] Hereinafter, an embodiment of the glass article of the present disclosure (hereinafter also referred to as "the present glass article") will be described in detail with reference to the drawings, but the present disclosure is not limited to the embodiment. In addition, the present disclosure can be implemented by any deformation without departing from the scope of the present disclosure.

[0015] <Glass Items> The glass article can be used as a vehicle glass such as a car, especially a window glass for a car, and can also be used in any position of the front, rear, side, and top of the car body. In addition, the glass article can also be used for purposes other than vehicles, such as buildings, etc. without restriction. In addition, as long as the glass article has the following structure at least in part, it can be used as a single glass including one glass substrate, or as a laminated glass including multiple glass substrates. The manufacturing method of the glass article is not particularly limited, but as described later, for example, it can be manufactured using a conventionally known float process.

[0016] This glass item is Figure 1A As shown in FIG. 1 , a coating film 2 and a shielding layer 3 are sequentially provided on a glass substrate 1. As described above, these layers may be sequentially laminated on at least a portion of one surface of the glass substrate, and these layers may or may not be laminated on the entire glass substrate constituting the glass article. For example, the coating film 2 may be disposed on the entire glass substrate, or may be disposed on a plurality of layers. Figure 1BAs shown, the frame-shaped shielding layer 3 is arranged on the coating film at a position that becomes the peripheral edge of the glass substrate. In addition, within the scope of the effect of the present disclosure, other layers may be provided between the layers, such as a color adjustment layer for adjusting the color tone, a heat insulation film layer, a UV cut-off film layer, etc. However, from the viewpoint of peeling resistance and whitening resistance, the present glass article is preferably composed of a glass substrate 1, a coating film 2, and a shielding layer 3. In addition, Figure 1A and Figure 1B are schematic diagrams of an embodiment of the glass article, Figure 1A A schematic cross-sectional view thereof is shown, Figure 1B A schematic front view thereof when viewed from the shielding layer 3 side is shown.

[0017] In this glass article, Figure 2 As shown, the existence ratio (porosity) of the pores 4 at the interface portion 5 between the coating film 2 and the shielding layer 3 is 24% or less. If the porosity is 24% or less, the adhesion of each layer after heat forming (hereinafter sometimes referred to as initial adhesion) and the adhesion after a certain period of use (hereinafter sometimes referred to as long-term adhesion) are excellent, and the whitening of the glass article can be suppressed. In addition, from the viewpoint of initial adhesion and long-term adhesion, the above-mentioned porosity is preferably 22% or less, more preferably 15% or less, and further preferably 10% or less. In addition, the porosity at the above-mentioned interface portion is preferably 0.5% or more. If the porosity is 0.5% or more, light scattering occurs due to the extremely small pores existing in the interface portion, and the absorption of sunlight energy by the shielding layer portion becomes smaller than when the above-mentioned pores do not exist, and the rise in glass temperature is easily suppressed. As a result, the risk of burns caused by glass contact, etc. can be further reduced, and the comfort inside the vehicle can be further improved. In addition, from the same viewpoint, the porosity of the above-mentioned interface portion is more preferably 1.0% or more. In addition, Figure 2 This is an example of a cross-sectional SEM image of the glass article of the present disclosure produced in Example 3 described later.

[0018] The range of the interface portion 5 between the coating film 2 and the shielding layer 3 for measuring the porosity can be set appropriately according to the thickness of the coating film and the shielding layer as long as it is near the interface between the coating film 2 and the shielding layer 3. In this embodiment, the porosity is measured in the thickness range of 2.5 μm from the surface of the coating film 2 toward the shielding layer side as the above-mentioned interface portion 5. The specific method for measuring the porosity will be described later.

[0019] Thus, the glass article with a specific porosity has excellent peeling resistance and whitening resistance, excellent adhesion between the coating film and the shielding layer, can suppress the occurrence of layer peeling and whitening caused by the pores, and has an excellent appearance. Therefore, even when the glass article is formed into a curved shape for a vehicle at a high temperature (e.g., 600 to 750° C.), it is easy to avoid the occurrence of peeling or whitening of the layers on the glass substrate.

[0020] In addition, the longest length of the pores 4 at the interface portion 5 between the coating film and the shielding layer is preferably less than 2.5 μm. If the longest length of the pores is less than 2.5 μm, the initial adhesion and long-term adhesion are excellent. In addition, from the same point of view, it is more preferred that the longest length of the pores is less than 1.5 μm. In addition, the longest length of the pores is preferably greater than 0.3 μm. If the longest length of the pores is greater than 0.3 μm, light scattering occurs due to the extremely small pores present in the interface portion, and the absorption of sunlight energy by the shielding layer portion becomes smaller than when the above-mentioned pores do not exist, making it easier to suppress the rise in glass temperature. As a result, the risk of burning caused by glass contact, etc. can be further reduced, and the comfort in the car can be further improved. In addition, from the same point of view, the longest length of the pores is more preferably greater than 0.5 μm. The specific method for measuring the longest length of the pores will be described later.

[0021] The porosity and the maximum length of the pores at the above-mentioned interface portion can be adjusted by, for example, changing the manufacturing conditions of the coating film (such as the mixture and type of process gas), the elemental composition of the shielding layer, the type of glass material contained in the shielding layer, the firing conditions (such as the heating rate), etc.

[0022] like Figure 2 As shown, in the present glass article, the pores 4 arranged on the glass substrate 1 are concentrated in the interface portion 5 between the coating film and the shielding layer (the portion with a thickness of 2.5 μm from the surface of the coating film toward the shielding layer side) compared to other parts of the glass article. Specifically, among the pores arranged on the glass substrate, preferably more than 30%, more preferably more than 50%, and further preferably more than 70% of the pores are concentrated in the interface portion between the above-mentioned coating film and the shielding layer. This is considered to be due to the following reasons. That is, when forming a coating film (for example, a dry coating film), the gas captured in the coating film (for example, the process gas in the dry coating: an inert gas such as Ar) is degassed from the coating film during heat forming at a high temperature. Then, it is believed that the material for forming the shielding layer is melted due to the heat forming, and the gas is retained near the interface between the coating film and the shielding layer, and finally pores are formed in this portion. The existence ratio (existence rate) of the above-mentioned voids at the interface portion can be calculated from any three cross-sectional SEM images used for measuring the porosity and the longest length of the voids described later, and the average value of the existence ratios of the voids obtained at the three locations is used.

[0023] In addition, if Figure 2 As shown, a plurality of pores 4 can be formed on the glass substrate of the glass article, but these pores can have uneven shapes. Specifically, the cross-sectional shape of the pores 4 when cut perpendicularly to the glass substrate 1 can be various shapes such as flat, polygonal, and irregular. In addition, the irregular shape here refers to an irregular and deformed shape, rather than a regular shape such as a circle, an ellipse, or a polygon. In this way, the shape of the pores formed on the glass substrate is not particularly limited, and can also be a deformed shape, as long as the above-mentioned porosity is within a specific range.

[0024] [Glass substrate] As the glass substrate (glass plate), a conventionally known glass substrate can be appropriately used, for example, heat absorbing glass, transparent glass, soda lime (soda lime) glass, quartz glass, borosilicate glass, alkali-free glass, green glass, UV green glass, etc. can be used. However, when the glass article is used as vehicle glass, the glass substrate is required to have a visible light transmittance that meets the safety standards of the country where the vehicle is used, and when used for other purposes, it is required to have the necessary characteristics in the purpose. Therefore, the glass substrate preferably adjusts the composition appropriately to achieve the required characteristics. As the composition of the glass substrate, it is expressed in mass % of an oxide basis, for example, the following composition can be cited. In addition, the composition of the glass substrate can be determined by fluorescent X-ray analysis. Silicon dioxide (SiO 2 ): 70-73% by mass Alumina (Al 2 O 3 ): 0.6 to 2.4 mass% Lime (CaO): 7-12 mass %, Magnesium oxide (MgO): 1.0-4.5 mass% R 2 O: 13-15 mass% (R is an alkali metal such as Na or K) Convert to Fe 2 O 3 Total iron oxide (T-Fe 2 O 3 ): 0 to 1.5 mass %.

[0025] In addition, the glass substrate can be substantially transparent, or can be given a color tone, i.e., colored. In addition, the glass substrate can be subjected to a strengthening treatment as required. As the strengthening treatment, it can be a chemical strengthening treatment, or it can be a physical strengthening treatment (air-cooling strengthening treatment).

[0026] In addition, the shape of the glass substrate is not particularly limited as long as it can be formed into a shape corresponding to the desired use, and for example, it can be rectangular. As the formed shape of the glass article, a curved shape can be exemplified, and the curved shape is not particularly limited, for example, it can be made into Figure 1A The glass article has a curved shape in the vertical direction of the paper shown. In addition, the glass article includes an article before the glass substrate provided with a coating film and a shielding layer is formed, and an article after the glass substrate is formed into a desired shape. Therefore, the glass substrate of the glass article can be a glass substrate before forming, for example, a rectangular shape, or can be a glass substrate after forming, for example, a curved shape. In addition, the forming of the glass article can be performed by forming a curved surface on the glass substrate by a bending process performed by heating, which is called firing bending, when the shielding layer is fired. In addition, the forming of the glass article can be performed by firing bending after forming the shielding layer, etc. on the glass substrate, or by firing bending after pre-firing once after forming the shielding layer, etc. In this way, the forming period of the glass article can be appropriately selected.

[0027] The thickness of the glass substrate can be set according to the purpose and is not particularly limited. For example, in the case of an automobile used in a vehicle, the thickness of the glass substrate is, for example, 0.2 to 5.0 mm, preferably 0.3 to 3.0 mm. In the laminated glass used in automobiles, especially the front window glass or the roof glass, from the viewpoint of strength such as anti-flying stone performance, the thickness of the glass substrate located on the outside of the car when installed on the car is preferably 1.1 mm or more, and more preferably 1.8 mm or more. In addition, from the viewpoint of lightweight laminated glass, the thickness of the glass substrate is preferably 3.0 mm or less, and more preferably 2.8 mm or less. In the laminated glass, from the viewpoint of operability, the thickness of the glass substrate located on the inside of the car when installed on the car is preferably 0.3 mm or more, and from the viewpoint of lightweight laminated glass, it is preferably 2.3 mm or less. In addition, the glass article can be used not only as a single glass, but also as a laminated glass, and can be used for various purposes. In addition, the thickness of the two glass substrates used in the laminated glass can be the same or different.

[0028] The glass substrate can be appropriately manufactured by a conventionally known method (eg, a float method, a fusion method, and a roll pressing method), and the manufacturing method is not particularly limited. In addition, a commercially available product can also be used as the glass substrate.

[0029] [Coating film] In the present glass article, a coating film 2 is disposed between a glass substrate 1 and a shielding layer 3 . The method of laminating the coating film on the glass substrate is not particularly limited. However, from the viewpoint of more effectively utilizing the excellent effects of the present disclosure, the coating film in this embodiment is preferably a dry coating film using a dry coating formed in a vacuum using a vapor phase growth method.

[0030] The dry coating includes physical vapor deposition (PVD) which is a physical film-forming method including vacuum evaporation and sputtering, and chemical vapor deposition (CVD) which is a chemical film-forming method.

[0031] The PVD method is mainly carried out in high vacuum (10 -1 ~10 -5 A method in which a film-forming substance that forms a thin film is evaporated and scattered into particles (atoms and molecules) by heating, sputtering, ion beam irradiation, laser irradiation, etc. under a state of Pa, and then attached and deposited on the surface of the substrate. Vacuum evaporation is a technique that heats a film-forming material such as a metal or metal oxide in a vacuum to melt, evaporate or sublime it, and causes the evaporated or sublimated particles (atoms and molecules) to adhere and accumulate on the surface of a substrate to form a thin film. In addition, sputtering refers to the technology of introducing an inert gas (mainly Ar) into a vacuum, applying a negative voltage to a target (e.g., a plate-shaped film-forming material) to generate a glow discharge, ionizing the inert gas atoms, and violently knocking the gas ions against the target surface at high speed, so that the particles (atoms and molecules) of the film-forming material constituting the target are violently ejected and adhere to and accumulate on the surface of the substrate to form a thin film. In the sputtering method, even materials that are difficult to use in vacuum evaporation methods such as high-melting-point metals or alloys can be formed into films, and a wide range of film-forming materials can be used.

[0032] On the other hand, the CVD method is carried out under atmospheric pressure to medium vacuum (100 to 10 -1 A method in which a gas raw material is introduced into the substrate under a pressure of 100 Pa (Pa) and energy such as heat, plasma, light, etc. is applied to stimulate and promote chemical reactions to synthesize thin films or fine particles and adsorb and deposit them on the surface of the substrate.

[0033] Among them, from the viewpoint of more effectively utilizing the excellent effects of the present disclosure, as the dry coating film, it is preferred to use a film selected from a heat ray reflective coating film, a low-emissivity coating film (Low-E film), a low-reflective coating film, and a p-polarized light reflective coating film. As a method for forming each film, a conventionally known method can be appropriately used.

[0034] The heat ray reflection coating film may be composed of more than one layer, for example, it may be composed of multiple layers (10 to 18 layers, etc.). Specifically, the heat ray reflection coating may include a dielectric layer, a functional layer, and a barrier layer. For example, the heat ray reflection coating film may be composed in the order of a first dielectric layer, a functional layer, a barrier layer, and a second dielectric layer from the glass substrate side. In addition, the functional layer may be composed of any one of Ag, Au, Cu, Al and Pt or a combination thereof. Among them, the functional layer is preferably composed of any one of Au, Cu, Al and Pt or a combination thereof. The dielectric layer and the barrier layer may be composed of any one of Ti, Zn, Sn, Si, Al and Ni or a combination thereof, respectively. In addition, the dielectric layer and the barrier layer may also be composed of oxides, nitrides or oxynitrides of these elements.

[0035] The low-emissivity coating film may be composed of more than one layer, for example, it may be composed of multiple layers (2 to 6 layers, etc.). Specifically, the low-emissivity coating film may include a dielectric layer and a functional layer. In addition, the dielectric layer and the functional layer may each be composed of one layer, or may be composed of multiple layers. For example, the low-emissivity coating film may be composed of a first dielectric layer, a functional layer, and a second dielectric layer in the order of a first dielectric layer, a functional layer, and a second dielectric layer from the glass substrate side. In addition, in this structure, the first dielectric layer, the functional layer, and the second dielectric layer may each be composed of one layer, or may be composed of multiple layers. In addition, the above-mentioned functional layer may be composed of any one of In, Sn, Al, Ni, Cr, and F, or a combination thereof. Alternatively, the functional layer may be composed of oxides, nitrides, or oxynitrides of these elements. The dielectric layer may be composed of any one of Si, C, Ti, Zr, Nb and Al or a combination thereof. In addition, the dielectric layer may be composed of oxides, nitrides or oxynitrides of these elements.

[0036] The low-reflection coating film may be composed of more than one layer, for example, may be composed of multiple layers (two layers, etc.). For example, the low-reflection coating film may be composed of a high-refractive layer and a low-refractive layer in the order of the glass substrate side. In addition, the low-refractive layer may be composed of Si, and the high-refractive layer may be composed of Ti. These refractive layers may also be composed of oxides, nitrides or oxynitrides of these elements.

[0037] The p-polarized light reflective coating film may be composed of more than one layer, for example, may be composed of multiple layers (two layers, etc.). For example, the p-polarized light reflective coating film may be composed of a high refractive layer and a low refractive layer in the order of the glass substrate side. Each layer may be composed of any one of Au, Ag, Cu, Si, Al, Zn, Zr, Sn, Nb, Ni, In, Ce, W, Mo, Sb, Bi and Ti or a combination thereof. In addition, the p-polarized light reflective coating film may also be composed of oxides, nitrides or oxynitrides of these elements.

[0038] The components (elements) constituting the coating film are not particularly limited, and may include, for example, Ag, Au, Cu, Pt, Ni, F, C, In, Sn, Ti, Nb, Ta, Zn, Al, In, Si, Cr, B and Zr, as well as nitrides, oxides and oxynitrides of these components. In addition, a plurality of these components may be included in combination. The composition of the coating film can be determined using energy dispersive X-ray spectroscopy (SEM-EDX). The acceleration voltage at this time can be appropriately set, but from the perspective of performing a more accurate measurement, it is preferably 5 to 25 keV, and more preferably 15 to 20 keV.

[0039] In addition, in the present glass article, the coating film is provided on at least a portion of one surface of the glass substrate. Therefore, the coating film may be in contact with the glass substrate, or another layer may be arranged between the glass substrate and the coating film so that the glass substrate and the coating film are not in direct contact.

[0040] The thickness of the coating film is not particularly limited, but from the viewpoint of imparting excellent various properties, the total thickness is preferably 25 to 500 nm, more preferably 50 to 450 nm, and even more preferably 100 to 400 nm.

[0041] [Occlusion layer] The shielding layer may be disposed on at least a portion of one surface of the glass substrate, specifically, on at least a portion of the coating film, but when the glass article is used as a glass article for a vehicle, it is preferably disposed so as to cover the peripheral edge of the glass substrate. The shielding layer prevents components mounted on the vehicle body or terminals of electrical components from being seen from outside the vehicle. In addition, the shielding layer may have various shapes such as a frame shape, a strip shape, or a dot shape. Figure 1B In the embodiment, the frame-shaped shielding layer 3 is provided on the peripheral portion of the glass substrate, more specifically, on the peripheral portion of the coating film 2. In addition, the shielding layer may be provided, for example, to cover a specific area from the edge of the glass substrate. More specifically, the shielding layer may cover a portion at least within 30 mm from the edge of the glass substrate (for example, within 50 mm from the edge).

[0042] The shielding layer contains crystalline components and may also contain pigments and additives (such as resins). In the shielding layer, from the viewpoint of allowing the gas retained at the interface between the coating film and the shielding layer to diffuse (degas) and suppress the generation of voids during heat forming, it is preferred to use a shielding layer with a high melting start temperature (melting point) of the crystalline component. Specifically, the melting start temperature of the crystalline component is preferably above 600°C. If the temperature is above 600°C, the viscosity at high temperature is small, so the gas retained at the interface between the coating film and the shielding layer can be actively diffused, and as a result, the formation of voids can be easily prevented. Therefore, it is easy to prevent the occurrence of whitening, in which the surface of the glass article looks white due to light scattering at the voids. Furthermore, by suppressing the formation of voids, the reduction in interface adhesion caused by the voids can be prevented, and the layer peeling caused by the different linear expansion coefficients of the coating film and the shielding layer can be prevented.

[0043] Furthermore, from the viewpoint of suppressing the formation of voids and preventing whitening, the resin decomposition (combustion) completion temperature of the shielding layer is preferably low, and specifically preferably 400° C. or lower.

[0044] The components (elements) constituting the shielding layer are not particularly limited, and for example, may include the following elements: Si, Bi, O, Fe, Ni, C, B, Al, Li, Na, K, Mg, Ca, Ba, Sr, Zn, Ti, Ce, Zr, Cu, Cr, Mn, and Co.

[0045] From the viewpoint of preventing the above-mentioned pore formation and whitening, it is preferred to adjust the composition in the shielding layer. Specifically, it is preferred that the composition ratio of Si (silicon) having the effect of increasing the above-mentioned melting start temperature and Bi (bismuth) having the effect of lowering the above-mentioned melting start temperature, that is, the Bi / Si ratio (mass %) in the above-mentioned shielding layer is above 3.9. If the Bi / Si ratio is above 3.9, it is possible to promote the degassing of the gas that forms the pores, reduce the porosity, and inhibit the whitening of the surface of the glass article. Furthermore, from the same viewpoint, the Bi / Si ratio is more preferably above 4.4, further preferably above 4.7, further preferably above 5.2, and particularly preferably above 6.3.

[0046] The composition of the shielding layer can be determined using energy dispersive X-ray spectroscopy (SEM-EDX). The acceleration voltage at this time can be set appropriately, but is preferably 5 to 25 keV, more preferably 15 to 20 keV, from the viewpoint of performing more accurate measurement.

[0047] The shielding layer (e.g., black ceramic layer) is a fired layer formed by applying a shielding layer forming material (ceramic paste) on a glass substrate, more specifically, on a desired position (e.g., on a peripheral portion) on a coating film, and heating and sintering at a high temperature. The firing temperature can be appropriately set, for example, to 500 to 700° C. (specifically, above 600° C.). The shielding layer forming material before firing may include glass frit (equivalent to the crystalline component when the shielding layer is formed), a pigment (e.g., a heat-resistant black pigment), and additives such as an (organic) carrier for dispersing the pigment as needed, a conductive metal, a reducing agent, a dispersing surfactant, a fluidity modifier, a fluidity auxiliary agent, an adhesion promoter, a stabilizer, and a colorant. In addition, as the shielding layer forming material, a commercially available product may also be used. By making the shielding layer into a fired layer, the shielding layer is bonded to the glass substrate.

[0048] The glass frit may contain, for example, one or more SiO 2 、Bi 2 O 3 Cr 2 O 3 , Cs 2 O、Na 2 O.B 2 O 3 , ZnO, TiO 2 ,La 2 O 3 , Nb 2 O 5 、MnO 2 、CeO 2 、MoO 3 , WO 3 , F, Al 2 O 3 、BaO、MgO、CaO、K 2 O and other components. In addition, it is known that glass frits having a high melting point range have excellent chemical resistance and a relatively low thermal expansion coefficient. SiO in glass frit 2 It forms a glass network and is also a crystallizing component. It also controls chemical, thermal, and mechanical properties and has the property of increasing the melting point of glass frit. 2 It may contain more than just SiO 2 , can also include, for example, Bi 4 Si 3 O 12 From the perspective of improving whitening resistance, the SiO 2 The content is preferably 10% by mass or more, more preferably 13% by mass or more. In addition, from the viewpoint of maintaining sinterability, the SiO in the shielding layer2 The content is preferably 30% by mass or less, more preferably 28% by mass or less. On the other hand, Bi in the glass frit 2 O 3 It is a component that forms a glass network and has the property of lowering the melting point. From the perspective of improving whitening resistance, Bi in the shielding layer 2 O 3 The content is preferably 60% by mass or less, more preferably 55% by mass or less. 2 O 3 The content is preferably 40% by mass or more, more preferably 43% by mass or more.

[0049] When forming the shielding layer, the glass frit may or may not have a different crystal form from the raw material stage (shielding layer forming material) before firing. In addition, the crystal component in the shielding layer may be composed of one glass frit or may be composed of multiple glass frits fused by, for example, firing.

[0050] In addition, the glass frit can be manufactured by a conventionally known method. For example, after mixing starting materials corresponding to the desired composition, melting them at a desired temperature and time, and cooling them with water or the like as needed, the glass frit having the desired composition can be manufactured. The glass frit can be ground into a desired particle size (for example, 1 to 8 μm) using a known grinding technique as needed. In addition, commercially available products can also be used as glass frit.

[0051] The content of glass frit in the shielding layer forming material can be set appropriately, but from the viewpoint of obtaining good sinterability, it is preferably 60% by mass or more, more preferably 65% ​​by mass or more, and further preferably 70% by mass or more. On the other hand, from the viewpoint of maintaining glass strength, the content of glass frit in the shielding layer forming material is preferably 99% by mass or less, more preferably 98% by mass or less, and further preferably 96% by mass or less. In addition, the content in the shielding layer forming material in this specification refers to the content of the total amount of inorganic components in the components constituting the shielding layer forming material, and does not take into account the content of organic components. Therefore, the glass frit content in the shielding layer forming material is the amount after removing the content of fillers, etc. contained in the shielding layer forming material.

[0052] As the above-mentioned pigment, known pigments in the past can be suitably used, for example, more than one pigment derived from composite inorganic pigments such as corundum-hematite, olivine, ruby, pyrochlore, rutile, spinel can be used. As pigment, for example, the metal oxide pigment (spinel pigment) containing copper (Cu), chromium (Cr), iron (Fe), cobalt (Co), nickel (Ni), manganese (Mn), aluminum (Al), magnesium (Mg), zinc (Zn), zirconium (Zr), niobium (Nb), yttrium (Y), tungsten (W), antimony (Sb) and calcium (Ca) etc. can be used. These black spinel pigments can be suitably used in the automobile industry, and in other industries such as building, household appliances and beverage industry, other metal oxide pigments producing other colors can be suitably used as pigment.

[0053] In addition, the spinel structure has the general formula AB 2 X 4 The conventional pigment structure, where X is usually O with approximately the same ionic radius 2- or F - Here, A and B represent the tetrahedral and octahedral sites in the standard spinel lattice. The spinel structure can be formed from many different elements, including the first row transition elements, making it the structure of most inorganic pigments. Most spinel compounds have a cubic space group, but distorted spinel structures can take on tetragonal and sometimes orthorhombic phases.

[0054] As a more specific example of the metal oxide pigment, CuO·CrO 3 ,CuCr 2 O 4 、(Co,Fe)(Fe,Cr) 2 O 4 、MnCr 2 O 4 , NiMnCrFe, CuCrMnO, and pigments modified by using modifiers to modify these pigments, etc. Here, the performance of the pigment can be determined by the raw materials, synthesis technology and conditions, and post-firing treatment. The pigment can be synthesized by a conventionally known method, such as the method described in Japanese Patent Publication No. 2019-509959, or a commercially available product can be purchased. The pigment can be formed by, for example, compounding or calcining a minute metal oxide or salt containing the target metal. In this case, the size of the minute metal oxide can be appropriately set, preferably 1 nm to 10 μm, more preferably 10 nm to 1 μm, and further preferably 50 to 500 nm.

[0055] In addition, as a pigment, a pigment derived from a rare earth manganese oxide pigment can also be used. For example, (YxMn)Oy, (LaxMn)Oy, (CexMn)Oy, (PrxMn)Oy, (NdxMn)Oy can be used. Here, in the above chemical formula, x is preferably 0.01 to 99, more preferably 0.08 to 12, and further preferably 0.25 to 4. In addition, in the above chemical formula, y is the number of oxygen atoms required to maintain electrical neutrality, preferably x+1 to 2x+2. As the pigment, CeMnO 3 、PrMnO 3 、NdMnO 3 And the pigments obtained by modifying these pigments with a modifier, etc. In addition, the rare earth manganese oxide pigment preferably has a gray titanium crystal structure or an orthorhombic crystal structure. By using the rare earth manganese oxide pigment, a high infrared reflectivity can be obtained, and the heating characteristics can be reduced. Moreover, the pigment does not contain cobalt material, so that hexavalent chromium will not be generated and dissolved even in acidic solutions such as acid rain.

[0056] The content of the pigment in the shielding layer forming material can be appropriately set, but from the viewpoint of obtaining the desired color tone, it is preferably 0.1% by mass or more, more preferably 1% by mass or more, further preferably 2% by mass or more, and particularly preferably 5% by mass or more. In addition, from the viewpoint of maintaining the sinterability of the shielding layer, the content of the pigment is preferably 50% by mass or less, more preferably 30% by mass or less, further preferably 25% by mass or less, and particularly preferably 15% by mass or less.

[0057] Examples of the organic vehicle for dispersing and suspending the glass frit and the pigment include vegetable oil, mineral oil, low molecular weight petroleum fractions, tridecanol, synthetic resins, and natural resins. As the conductive metal, for example, silver (silver particles) can be used. As the reducing agent, for example, silicon metal can be used. The dispersing surfactant plays a role in assisting the wetting of the pigment when using an inert particulate inorganic pigment. The dispersing surfactant usually contains a block copolymer having a group having affinity with the pigment, and also contains a solvent (e.g., xylene, butyl acetate, methoxypropyl acetate) as required. The dispersing surfactant can appropriately use a conventionally known surfactant, for example, Disperbyk 162 (trade name, produced by BYK Chemical Company) can be used. The flowability modifier is used to adjust the viscosity, and conventionally known materials can be appropriately used. For example, Viscobyk series (produced by BYK-Chemie GmbH) can be used. The flowability aid is an additive for adjusting viscosity and flowability, and a conventionally known additive can be used. For example, Additol VXW6388 (trade name, manufactured by UCB Surface Speciality Co., Ltd.) can be used. The adhesion promoter is used to improve the compatibility with the layer (coating film) on which the shielding layer is provided, and can be appropriately selected according to the composition of the coating film used. As the stabilizer, for example, a light stabilizer or a UV shielding agent can be used. In addition, the compounding amounts of these additives can be appropriately set and are not particularly limited.

[0058] The composition of the shielding layer (the entire shielding layer including glass frit, pigment, additives, etc.) is expressed in mass % based on oxides, and may be, for example, the following composition: The composition of the shielding layer may be considered to be the same as the composition of the shielding layer forming material before firing. Bi 2 O 3 : 40~60 mass% SiO 2 : 15 to 30% by mass Cr 2 O 3 : 5 to 25% by mass CuO: 3-8 mass% MnO 2 : 3-6 mass% Al 2 O 3 : 0.2~4% by mass MgO: 0-2 mass% CaO: 0-3% by mass BaO: 0-8 mass% Na 2 O: 0-5% by mass K 2 O: 0-3% by mass TiO 2 : 0-5% by mass ZnO: 0 to 8 mass %.

[0059] The thickness of the shielding layer affects the UV transmittance, acid resistance, weather resistance, concealment, glass strength, and cost. From the viewpoints of UV transmittance, acid resistance, weather resistance, concealment, etc., the thickness of the shielding layer is preferably 5 μm or more, more preferably 8 μm or more, and further preferably 10 μm or more. In addition, from the viewpoints of glass strength and cost, the thickness of the shielding layer is preferably 30 μm or less, more preferably 20 μm or less, and further preferably 15 μm or less. The thickness of the shielding layer can be determined using a scanning electron microscope (SEM).

[0060] The firing conditions of the shielding layer can be appropriately set within the range that can obtain the effect of the present invention. In other words, it can be appropriately set within the range that satisfies the above-mentioned porosity of 24% or less. For example, the firing speed (conveying speed) (mm / s) and firing temperature (°C) when conveying the treated object (to which the shielding layer forming material is applied) in the automobile glass forming process can be adjusted, and when the firing temperature is changed during firing, its temperature distribution can be adjusted. For example, the firing time can be 3 to 30 minutes (preferably 4 to 20 minutes), and the firing temperature can be 550 to 730°C (preferably 580 to 710°C, more preferably 600 to 710°C).

[0061] <Method for manufacturing glass article> The method for producing the glass article of the present invention is not particularly limited, and the glass article can be produced, for example, by a production method including the following steps. A step of preparing a glass substrate (substrate preparation step). A step of forming a coating film on a glass substrate (coating film forming step). A step of forming a shielding layer on the coating film (shielding layer forming step).

[0062] The substrate preparation step (substrate production step) may include a step of melting glass raw material and pouring the melted glass raw material into a tin bath (melting step) and a step of slowly cooling the melted glass raw material (slow cooling step).

[0063] The shielding layer forming step may include the following steps, for example. A step of preparing a material for forming a shielding layer (a step of preparing a material for forming a shielding layer). A step of applying the above-mentioned shielding layer forming material on the coating film (coating step). A step of sintering the shielding layer forming material applied on the coating film (sintering step).

[0064] In addition, the above-mentioned manufacturing method may include the following steps. A step of heat-forming the glass substrate on which the coating film and the shielding layer are sequentially arranged into a desired shape (heat-forming step). A step of cooling the heat-formed glass substrate (cooling step). These steps may be performed sequentially, or a plurality of steps (for example, a shielding layer forming step (specifically, a sintering step) and a heat forming step) may be performed simultaneously. The above-mentioned manufacturing method will be described in detail below.

[0065] First, a glass substrate (glass plate) of, for example, a rectangular shape is prepared (substrate preparation step). At this time, the glass substrate may be purchased from a commercial product or may be prepared, for example, by the following method. That is, glass raw materials mixed into a desired glass composition are heated at a predetermined temperature to obtain molten glass. Next, the obtained molten glass is poured into a tin bath filled with molten tin (melting step), formed into a plate-shaped glass ribbon and slowly cooled (slow cooling step) to obtain a glass substrate. At this time, the obtained glass ribbon may be subjected to processing (for example, SO 2 Treatment or cleaning treatment). The forming of the glass substrate can be carried out in any of the above-mentioned melting process and slow cooling process. In addition, when making the glass substrate, it can be appropriately cut into a desired size. For example, when the vehicle glass is used as a front window glass for an automobile, a glass substrate of (500 to 1300 mm) × (1200 to 1700 mm) × (1.6 to 2.5 mm) is prepared. The glass substrate can be a single piece or a laminated glass formed by bonding two or more pieces of glass.

[0066] Next, a coating film is formed on at least a portion of one surface of the glass substrate, for example, on the entire surface of the glass substrate (coating film forming step). The coating film forming conditions can be appropriately selected according to the type of coating film to be produced. For example, when forming a low-emissivity coating film (Low-E film) as the coating film, Ar gas, O 2 Gas and N 2 Any one of the gases or a mixed gas thereof is used as a process gas and formed by sputtering.

[0067] Then, a frame-shaped shielding layer is formed on at least a portion of the coating film, for example, on the peripheral portion of the coating film (shielding layer forming step). Specifically, a shielding layer forming material (for example, a colored ceramic paste) is applied to at least a portion of the glass substrate on which the coating film is formed (coating step), and dried as needed. There is no particular limitation on the coating method of the shielding layer forming material, and for example, screen printing, inkjet printing, electronic printing, etc. can be used. Specifically, it is preferred to print on the glass substrate using a #150 to #250 mesh screen.

[0068] The shielding layer forming material may be a commercially available product or may be prepared separately (shielding layer forming material preparation step). The shielding layer forming material may be prepared, for example, by dispersing the above-mentioned desired glass frit and pigment in an organic vehicle.

[0069] Next, the obtained glass substrate is heated to a predetermined temperature using a firing furnace such as an IR furnace, and the shielding layer forming material is sintered on the glass substrate (sintering process). The heating (firing) temperature is not particularly limited, and is, for example, 500 to 730° C. (preferably 550 to 700° C.). In addition, the firing speed (conveying speed) is also not particularly limited, and is preferably 5 to 30 mm / s. In addition, the heating time is, for example, 3 to 30 minutes (preferably 4 to 20 minutes). Thus, a shielding layer is formed on the glass substrate.

[0070] Among them, since the glass frit in the shielding layer forming material has various characteristics, one glass frit may be used, or two or more glass frits may be mixed and used. In addition, two or more glass frits of the same composition with different particle sizes may be mixed and used as appropriate. From the viewpoint of reducing the porosity, the melting point of the glass frit is preferably above 600°C, more preferably above 630°C. In addition, from the viewpoint of adhesion to glass, the melting point of the glass frit is preferably below 700°C, more preferably below 680°C. When two or more glass frits are mixed and used, it is preferred that the softening point of at least one of the glass frits is within the above range, and it is more preferred that the softening points of all the glass frits are within the above range.

[0071] Next, the glass substrate on which the coating film and the shielding layer are sequentially arranged is heated and formed into a desired shape (heating and forming step), and a cooling operation is performed as needed (cooling step). Alternatively, the glass substrate may be formed into a desired shape by self-weight bending or press bending while being maintained at the heating temperature in the sintering step. That is, the heating and forming step and the sintering step may be performed in parallel. In press bending, for example, a glass plate is bent using a pressurizing device (heating and pressing device) according to the desired shape of the automobile window glass. In self-weight bending, the glass substrate is bent using a self-weight bending device. Furthermore, air cooling and tempering can be performed according to the safety standards required for automobile window glass.

[0072] The glass article thus obtained has excellent durability, can suppress the peeling or whitening of each layer on the glass substrate, and has excellent appearance. In addition, the glass article does not use whisker-shaped refractory materials, can take into account the low-temperature sintering property of the shielding layer forming material and the high plate strength of the glass article. Example

[0073] The present disclosure is described in more detail below using a plurality of examples, but the present disclosure is not limited to these examples. Examples 1 to 7 are embodiments of the present glass article, and Examples 8 to 10 are comparative examples. Figure 2 and Figure 3Partial cross-sectional SEM images of the glass articles produced in Examples 3 and 8 are shown respectively.

[0074] [Example 1] (Example 1-1) Preparation of glass substrate and production of coating film A low-emissivity coating film is formed on one surface of a glass substrate using a sputtering device. Specifically, first, a glass substrate with a thickness of 2.1 mm (trade name: FGY1, produced by AGC Co., Ltd.) is prepared. Then, a titanium oxide layer containing zirconium oxide is formed on the surface of the glass substrate by sputtering. The film is formed using a zirconium oxide-doped titanium dioxide target with a zirconium oxide content of 35% by mass, and the film thickness is targeted to be 10 nm. Then, a silicon dioxide layer is formed by sputtering. The film thickness is targeted to be 35 nm. Subsequently, an ITO (indium tin oxide) layer is formed by sputtering. The film thickness is targeted to be 120 nm. After that, a silicon dioxide layer is formed. The film thickness is targeted to be 70 nm. Finally, a silicon dioxide layer containing zirconium oxide is formed on the surface of the obtained glass substrate by sputtering. The film is formed using a zirconium oxide-doped silicon dioxide target with a zirconium oxide content of 10% by mass, and the film thickness is targeted to be 20 nm. Through the above steps, a glass substrate with a coating film is obtained. In addition, Ar or O is used during film formation of each layer. 2 or a mixture thereof.

[0075] (Example 1-2) Production of shielding layer A shielding layer having the element composition (mass %) shown in Table 1 was prepared on the glass substrate, specifically on the periphery of the coating film. Specifically, a shielding layer forming material having the element composition was printed on the periphery of the coating film by a #150 to #250 mesh screen printing method and dried. Next, a sintering furnace (IR furnace) was used to sinter the shielding layer forming material on the glass substrate under the following sintering conditions A to form Figure 1B The shielding layer is in the shape of a frame shown. The thickness of the shielding layer is 15 μm. In this way, a glass article having a coating film and a shielding layer in this order on a glass substrate was produced. ·Firing conditions A The temperature was raised to 630°C at a rate of 3°C / second, and after reaching 630°C, the calcination temperature was maintained at 630°C. The total calcination (heating) time was 240 seconds.

[0076] [Example 2~Example 10] In Examples 2 to 10, the elemental composition (mass %) of the shielding layer is shown in Table 1. In addition, glass articles were produced in the same manner as in Example 1 except that the firing conditions were changed to the firing conditions shown in Table 2, and were evaluated according to the evaluation method described below to measure the values ​​of various physical properties. Among them, the specific elemental composition (mass %) of the shielding layer described in Example 6 is as follows: Bi: 36.1, Si: 8.2, O: 29.1, Cr: 12.4, Cu: 5.5, Mn: 4, Na: 1.2, Al: 0.6, Ti: 0.4, K: 0.2, C: 2.3 (total 100). In addition, the details of each firing condition shown in Table 2 are as follows. ·Firing conditions AA The temperature was increased at 2°C / sec to 300°C. After reaching 300°C, the temperature was increased at 3.7°C / sec. After reaching 630°C, the calcination temperature was maintained at 630°C. The total calcination (heating) time was 240 seconds. ·Firing conditions B The temperature was raised to 630°C at a rate of 4.5°C / second, and after reaching 630°C, the calcination temperature was maintained at 630°C. The total calcination (heating) time was 240 seconds.

[0077] <Measurement methods of physical properties> The methods for measuring the physical properties of the obtained glass article are as follows.

[0078] [Porosity] The porosity of the interface portion of the coating film and the shielding layer stacked on the glass substrate is determined according to the following method. That is, for the three randomly selected cut surfaces of the obtained glass article when cut perpendicularly to the surface of the glass substrate, a scanning electron microscope (SEM) (trade name: TM4000Plus, manufactured by Hitachi, Ltd.) is used to obtain images with a magnification of 2000 times. Then, the three cross-sectional SEM images obtained are processed using commercially available image analysis software (trade name: WinRooF2018, manufactured by Mitani Shoji Co., Ltd.), and the proportion of pores (gaps) that appear black is calculated based on the contrast difference. Specifically, in the cross-sectional SEM image, the ratio of the total pore cross section in the cross section within the range of 2.5 μm thickness from the interface between the coating film and the shielding layer to the shielding layer side and 60 μm width at any part of the glass substrate. Then, the average value of the pore ratio at the three locations is calculated, which is the porosity (%). The results of each example are shown in Table 2. In Examples 1 to 10, 70% or more of the pores formed in the glass substrate were present in the interface portion.

[0079] [Longest length of hole] When measuring the porosity, the length of each hole parallel to the surface of the glass substrate in the three cross-sectional SEM images obtained was measured, and the longest hole length was the longest hole length (μm).

[0080] [Shielding layer composition] The elemental composition of the shielding layer used in each glass article of each example was determined by the following method. That is, the surface of the sample (shielding layer) was measured by energy dispersive X-ray spectroscopy (SEM-EDX) to quantify the composition (mass %) of each component (element). At this time, as a scanning electron microscope (SEM), a product name: TM4000Plus, manufactured by Hitachi, Ltd., was used, and as an EDX, a product name: AZtecOne, manufactured by Oxford Instruments, Inc. was used. The results of each example are shown in Table 1.

[0081] [SiO 2 content] The SiO contained in the shielding layer of the glass article used in each example was measured by SEM-EDX. 2 Table 2 shows the results of each example.

[0082] [Bi / Si ratio] The Bi / Si mass % ratio in the shielding layer of each example was calculated based on the shielding layer composition determined by the above SEM-EDX. The results of each example are shown in Table 2.

[0083] <Evaluation Method> The obtained glass articles were evaluated using the following evaluation methods.

[0084] [Initial adhesion and long-term adhesion evaluation] For the glass articles made in each example, the adhesion was evaluated (initial adhesion) by the checkerboard test (cross cut test) method described in JIS K 5400. In addition, the glass articles made in each example were stored in a high temperature environment (temperature: 80°C) for 30 minutes and then stored in a low temperature environment (temperature: -30°C) for 30 minutes for 100 cycles and 500 cycles (hot and cold test) (this is considered as 1 cycle). Then, the above-mentioned checkerboard test (long-term adhesion) was also performed on the glass articles that had undergone the hot and cold test. The results of the checkerboard test of the glass articles just made and the glass articles after the hot and cold test (the above-mentioned 100 cycles and 500 cycles) were evaluated according to the evaluation criteria described in JIS K 5400 with 6 levels of 10 / 8 / 6 / 4 / 2 / 0. The evaluation results of each example are shown in Table 2.

[0085] [Evaluation of Melting Onset Temperature of Crystalline Component] The melting start temperature of the crystalline component (sintered) used in the shielding layer used in Examples 1 and 8 was measured by using a thermogravimetric differential thermal analyzer (TG-DTA) (trade name: Q650, manufactured by TA Instruments) at a temperature of 10°C / min to 800°C. The results showed that the melting start temperature of the melt of Example 1 was 610°C, as shown in Table 2, the porosity was low, and whitening did not occur. On the other hand, the melting start temperature of the glass frit of Example 8 was 580°C, as shown in Table 2, the porosity was high, and whitening occurred.

[0086] [Whitening evaluation] The degree of whitening of the glass article (particularly the shielding layer portion) of each example was evaluated according to the following evaluation criteria. The evaluation results are shown in Table 2. Evaluation criteria 3: Whether observed under fluorescent light or high-brightness LED flashlight, no holes were confirmed on the surface of the glass article, and the whitish portion of the surface did not exist. 2: Although it was not confirmed under fluorescent light, when using a high-brightness LED flashlight, it was confirmed that there were holes on the surface of the glass object, and light was scattered in the holes, making it appear white. 1: Even under a fluorescent light, holes are observed on the surface of the glass article, and the holes scatter light and appear white. The hue was measured by measuring the lightness index L* value of the CIE1976 (L*a`*) color space (CIELAB) according to JIS Z8722 (2000). The colorimeter was CR-400 manufactured by Konica Minolta, and the light source was set to CIE standard auxiliary colored light source C and the measurement diameter was set to 8 mm. The L value of the surface of the glass article of Example 4 was 25, and the L value of the surface of the glass article of Example 7 was 24.

[0087] Table 1 element Example 1, 2 Example 3 Example 4, 8 Example 5 Example 6 Example 7 Example 9 Example 10 Bi 40.8 37.3 39 40.2 36.1 38.3 29.6 50.8 Si 6.5 7.2 10.5 8.6 8.2 9.9 8.4 3.6 the remaining 52.7 55.5 50.5 51.2 55.7 51.8 62 45.6 total 100 100 100 100 100 100 100 100 Table 2

[0088] In summary, the glass article having a specific porosity has excellent peeling resistance and whitening resistance, excellent adhesion between the coating film and the shielding layer, can suppress the occurrence of layer peeling and whitening caused by pores, and has an excellent appearance.

[0089] This application claims the benefit of priority based on Japanese patent application No. 2022-123521, filed on August 2, 2022, the disclosure of which is incorporated herein in its entirety. Explanation of symbols

[0090] 1Glass substrate 2 coating film 3 shielding layer 4 empty holes 5. Interface between coating film and shielding layer.

Claims

1. A glass article having a coating film and a shielding layer in sequence on a glass substrate, The porosity at the interface between the coating film and the shielding layer is 24% or less.

2. The glass article according to claim 1, wherein: The longest length of pores at the interface between the coating film and the shielding layer is 2.5 μm or less.

3. The glass article according to claim 1, wherein: The Bi / Si ratio in the shielding layer is above 3.

9.

4. The glass article according to claim 2, wherein: The Bi / Si ratio in the shielding layer is above 3.

9.

5. The glass article according to claim 3 or 4, wherein: The Bi / Si ratio in the shielding layer is above 4.

7.

6. The glass article according to claim 3 or 4, wherein: The melting start temperature of the crystalline component constituting the shielding layer is 600° C. or higher.

7. The glass article according to any one of claims 1 to 4, wherein The coating film is a dry coating film.

8. The glass article according to claim 7, wherein: The dry coating film is a film selected from a heat ray reflecting coating film, a low-emissivity coating film, a low-reflection coating film, and a p-polarized light reflecting coating film.

9. The glass article according to claim 7, wherein: The pores disposed on the glass substrate are concentrated in the interface portion between the coating film and the shielding layer compared to other portions.

10. The glass article according to claim 7, wherein: The holes arranged on the glass substrate have non-uniform shapes.

11. The glass article according to claim 10, wherein: The cross-sectional shape of the holes when cut perpendicularly to the glass substrate is a flat shape, a polygonal shape, or an irregular shape.

12. The glass article according to any one of claims 1 to 4, wherein It is used as window glass for automobiles.

13. The glass article according to claim 7, wherein: It is used as window glass for automobiles.

Citation Information

Patent Citations

  • Modified black spinel pigments for glass and ceramic enamel applications

    JP2019509959A

  • Travel control method and travel control device for vehicle

    JP2022123521A

  • Chemically durable, low-e coating compatible black enamel compositions

    WO2021107707A1